(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
نفذ البحث خلال الموسمين الزراعيين 2009-2010 في مركز البحوث العلمية الزراعية في الغاب لدراسة تأثير ثلاث أعماق للحراثة (حراثة سطحية غير قلّابة 0-20 سم، حراثة متوسطة قلّابة 0-30 سم، حراثة عميقة قلّابة 0- 40 سم) وثلاثة كثافات نباتية ( 66667, 88889 ، 133333) نبات/ه في بعض مكونات الغلة لمحصول القطن (السلالة 124) وإنتاجيته ، صممت التجربة بطريقة القطاعات المنشقة بثلاثة مكررات، وبينت الدراسة تفوق الحراثة العميقة معنوياً على الحراثة المتوسطة والسطحية في الصفات المدروسة، ووصل الفرق في الإنتاجية كغ/هـ (652.33 ، 1673.33 ) كغ/هـ في الموسم الأول على التوالي وإلى (424.33، 960.67) كغ/هـ في الموسم الثاني لصالح الحراثة العميقة. تفوقت معنوياً الكثافتان النباتيتان (66667, 88889 ) نبات/ه معنوياً على الكثافة النباتية (133333 ) نبات/ه في الصفات المدروسة في الموسمين الزراعيين ووصل الفرق في الإنتاجية إلى (514.67، 423.67) كغ/هـ على التوالي في الموسم الأول وإلى ( 407، 284 ) كغ/هـ في الموسم الثاني. أعطى التفاعل بين معاملات أعماق الحراثة والكثافة النباتية أفضل القيم عند معاملة الحراثة العميقة (0-40) سم مع الكثافة النباتية (66667) نبات/ه، حيث تفوقتا معنوياً في كافة مكونات المحصول (الفروع الخضرية والثمرية، عدد الجوزات المتفتحة، وزن الجوزة) مقارنة مع بقية المعاملات. The research was carried out during 2009 and 2010 Agricultural seasons in AI -Ghab Research Center to study effect of three tillage depths (no tipper surface plowing 0-20 cm, tipper medium plowing 0 -30 cm and tipper deep plowing 0 -40 cm), three plant densities (66667, 88889 and 133333) plant/h on some Yield’s components and productivity of cotton crop (strain 124). The experiment was laid out in split-plot design (SPD) by using three replications. The study showed, the tipper deep tillage increased significantly in studied characteristics compared to tipper medium plowing and no tipper plowing surface, the differences in productivity were (1673.33 ،652.33) kg/h in the first season and (424.33, 960.67) kg/h in the second season, respectively. The two plant densities (66667-88889) plant/h increased significantly in studied characteristics compared to the plant density (133333) plant/h, the differences in productivity were (423.67،514.67) kg/h in the first season and (407, 284) kg/h in the second season, respectively. The interaction between treatments of tillage depths and plant density resulted in deep plowing (0 -40 cm) and plant density (66667) plant/h, which increased significantly in the all of crop components (vegetative and fruiting branches, open bolls, Boll weight) compared to other treatments.